Effect of autologous growth factors on apoptosis and thickness of the outer nuclear layer in an experimental retinal degeneration model. (1st November 2020) - Ozmert, Emin; Demirel, Sibel; Arslan, Umut; Biçer, Özlem; Ahlat, Ozan; Şermet, Figen
Abstract: Retinal pigment epithelium and photoreceptor cells are a microenvironment where 90 different peptides are synthesized for transduction, visual cycle, intracellular electron transport chain, and removal of metabolic wastes. Depending on the inheritance pattern, either mutant proteins accumulate inside the cells or the energy cycle is disrupted. Disruption of homeostasis causes the cells to switch to the dormant phase; if the improper conditions last longer, then apoptosis eventually develops resulting in a loss of visual function. In neural tissues, growth factors such as neural growth factor, brain-derived neurotrophic factor, ciliary neurotrophic factor, and insulin-like growth factor are regulatory peptides for intracellular energy cycle and intracellular digestion. In this study, it has been shown histopathologically that autologous growth factors can prevent apoptosis and prevent loss of outer retinal thickness in the retinal degeneration model created with sodium iodate.